Hazard Identification and Risk Assessment for Machinery LiftingUsing All Terrain Cranes (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
Lifting and transporting machinery using rubber-tired cranes is an essential activity in various industries such as construction, transportation, and manufacturing. Cranes are used to lift and move heavy materials or equipment. However, the use of such cranes involves high risks, with the potential for accidents that may result in injury or death. This study focuses on identifying hazards and assessing risks in the operation of lifting and transporting machinery using rubber-tired cranes, using the Job Safety Analysis (JSA) technique. The research findings indicate that various processes, such as preparing the crane setup area, determining the setup points, testing operations, and pre-lifting safety checks have risk at high level. Risk control measures must be reviewed to prevent accidents. In-depth interviews revealed the causes of accidents stemming from factors such as unstable crane setup, overloading, and operator errors. These issues can be addressed through technical controls, continuous training, risk assessments, maintenance measures, and appropriate environmental management. Adhering to safety standards can significantly reduce accidents and enhance operational safety effectively.